2020
DOI: 10.22146/jnteti.v9i4.648
|View full text |Cite
|
Sign up to set email alerts
|

Desain dan Implementasi Sistem Pencatatan Pemungutan Suara dengan Teknologi Blockchain pada Jaringan Peer-to-Peer

Abstract: Proses voting (pemungutan suara) merupakan salah satu bagian penting dalam sistem demokrasi, yang sampai saat ini masih banyak dilakukan secara konvensional menggunakan kertas. Pelaksanaan kegiatan voting yang dikelola oleh satu pihak atau organisasi membuat data hasil voting rentan manipulasi. Blockchain sebagai sebuah teknologi yang mampu menjaga keamanan data dapat dijadikan sebagai salah satu solusi untuk mengatasi kecurangan dalam proses voting. Data hasil voting dicatat di dalam blockchain, kemudian data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…We are creating and implementing blockchain technology to be used in voting on peer-to-peer networks with the success of sending block data from one node to another efficiently and quickly in terms of quality and security [9]. Blockchain technology can be helpful in an e-certificate system, where technology created using a distributed database with blockchain transaction data maintains security in the flow and privacy of data so that it is not easily imitated [9]. We are designing an electronic voting system that utilizes Blockchain technology in a website-based application.…”
Section: Methodsmentioning
confidence: 99%
“…We are creating and implementing blockchain technology to be used in voting on peer-to-peer networks with the success of sending block data from one node to another efficiently and quickly in terms of quality and security [9]. Blockchain technology can be helpful in an e-certificate system, where technology created using a distributed database with blockchain transaction data maintains security in the flow and privacy of data so that it is not easily imitated [9]. We are designing an electronic voting system that utilizes Blockchain technology in a website-based application.…”
Section: Methodsmentioning
confidence: 99%
“…By embracing blockchain in the conveyance of information bases on e-casting a ballot frameworks can diminish one of the conning wellsprings of data set control. [7] The above proposed systems do not identify its users with the simplicity and compatibility of the its process as the majority being ill-educated. The systems are complex and require explicit tutoring and monitoring for efficient working of the system.…”
Section: Litereature Surveymentioning
confidence: 99%
“…We can see that blockchain technology has impacted the education system and learning system [28]. Because of the (ACE Report), Ted Mitchell wrote a statement that there is a connected impact in the world of education and the workforce to create effectiveness and efficiency of technology in the research of [29]. The revealed that a system with digital-based rights management included in blockchain technology could be a solution in managing to record, storing, and digitally verifying certificates with guaranteed security [30].…”
Section: Eternalmentioning
confidence: 99%